Free radical scavenging activity and lipid peroxidation inhibition of Hypericum helianthemoides (spach) Boiss - Soheila Moein; Mahmoodreza Moein; Fatemeh Farmani (Shiraz University of Medical Sciences, 2015)
Antioxidants are compounds that obstruct the oxidation of macromolecules in the body. In general, there are two categories of antioxidants, natural and synthetic. Recently, interest has been increased considerably for obtaining new natural antioxidants. In this study, the scavenging of free radicals such as DPPH, NO and OH by Hypericum helianthemoides extract was evaluated. Also, the antioxidant properties of this extract were evaluated by FRAP, FTC methods and determination phenolic compounds. The plant was collected from north of Fars Province and plant extraction was obtained using ethanol. In DPPH radical scavenging, different concentrations of the Hypericum extract were added to DPPH radical. In hydroxyl radical scavenging, Fenton reaction mixture, TCA and TBA were mixed with Hypericum extract. In nitric radical scavenging, nitropruside was mixed with Hypericum extract and then sulphanilic acid, naphthylene diamine were added. In determination of phenolic compounds, Folin-ciocalteu and sodium carbonate were added to Hypericum extract. In DPPH radical scavenging, the IC50 of Hypericum extract (309.35±6.5μg/ml) was higher than the antioxidant standards, BHT (IC50=81.9±2.6 μg/ml) and quercetin (IC50=60.04±6.48 μg/ml). The highest scavenging of hydroxyl radicals was observed in Hypericum extract (70.3±0.8%, 125 μg/ml). In gallic acid it was (73.8±3.3%). In 200 μg/ml of Hypericum extract scavenged NO radical (85.2±2.7%). In FRAP method, the IC50 of this extract was 109.7±10.5 μg/ml. In FTC method, the inhibition of lipid peroxidation by Hypericum extract, BHT and ascorbic acid were 59.2±2.2, 66.9±0.15, 64.06±0.02 respectively. Total phenol of the plant extract was 3±0.4 mg/g.